Silt pit efficiency in conserving soil water as simulated by HYDRUS 2D model - Bohluli, Mohsen; Teh, Christopher Boon Sung; Mohd Hanif, Ahmad Husni; Abdul Rahman, Zaharah (Universiti Putra Malaysia Press, 2014)
Silt pit is one of the recommended soil water conservation practices in oil palm plantations. It is commonly regarded that the larger and deeper the silt pit, the more effective the pit would be to conserve soil water. This hypothesis was tested in this paper, where the effectiveness of four silt pit dimensions on conserving soil water in the oil palm active rooting zone was simulated using the HYDRUS 2D model. These silt pits had different sizes and total wet wall-to-floor area ratio (W:F): H1 silt pit (1x1x1 m of width, length, and depth, respectively, and W:F ratio of 4.0), H2 (1.5x1x1 and W:F of 2.5), H3 (2x1x0.5 and W:F of 1.5) and H4 (2Ã—1Ã—2 and W:F of 1.5). Simulations showed that silt pits with larger W:F ratios could store water for longer periods and feed water to a farther horizontal distance within the soil compared to silt pits with smaller W:F ratios. H1 took the longest to dry out, whereby it took 14 to 19 hours longer to dry out compared to than H2, H3 and H4. H1 and H3 could feed water as far as 80 cm away from the pit more than H2 and H4 (60 and 50 cm, respectively). This is because silt pits with larger W:F ratios had larger horizontal water flow than the vertical water flow. Meanwhile, the depth of a silt pit should not be below the oil palm active rooting depth, which water would flow out of reach by the roots. This study is a preliminary work to a field experiment where simulations from this paper would be validated against measurements obtained in the field before recommending the use of silt pits and their size to be constructed in oil palm plantations.